Evaluación de microorganismos de montaña y pro biótico comercial, en lechones de pre-cría en el cantón Babahoyo - Cadena Valero, Brhian Fabián (2019)
SUMMARY The present work was carried out in the san pablo experimental farm of the faculty of agricultural sciences of the Babahoyo technical university. The work lasted 42 days, the object of the work was the evaluation of two levels of mountain microorganisms plus commercial probiotic with doses of 10 and 20%. In pre-breeding piglets they were not immunized at any time and the use of antibiotics was eliminated throughout the duration of the work, a completely randomized design system was used with three treatments and four repetitions with eight pigs per treatment and two for each repetition, thus forming eight experimental units with a total of 24 pigs. The verification of the measurement of the treatments was carried out with the Tucker test (P˂0,05), the statistical program InfoStat was used. The variables studied were: Average weekly weight, weekly food consumption and food efficiency. In the samples taken from average weekly weight, no statistical difference (p˃0.05) was found between the means of the treatments. The T3 treatment gave better results with weights of (21.64 kg). In the parameters of food consumption, the results obtained are shown by verifying that the variable of food consumption did register that the treatment 2. T2 (0.34 kg, 0.78 kg, 0.96), In the food efficiency parameters it was recorded that the T3 treatment. I present the best feed conversion with gains from week 2 to week 6 (0.62 kg, 1kg, 1.5kg, 1.88kg, 1.76kg,). Keywords: mountain microorganisms, probiotic, pre-breeding